Investment Behavior of Working Women in India: A Case Study of Sri Ganganagar District (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This paper explores the investment behavior of working women in Sri Ganganagar District, India. It investigates the factors influencing their investment decisions, the types of investment avenues preferred, and the impact of socio-economic variables on their investment behavior. The study includes a hypothesis test to analyze the relationship between education level and investment preferences. The findings aim to provide insights for financial advisors and policymakers to better cater to the financial needs of working women in this region.